Positive modulation of the a9a10 nicotinic cholinergic receptor by ascorbic acid - Boffi, Juan Carlos (2013)
Background and Purpose: The activation of α9α10 nicotinic cholinergic receptors (nAChRs) present at the synapse between efferent olivocochlear fibres and cochlear hair cells can prevent acoustic trauma. Hence, pharmacological potentiators of these receptors could be useful therapeutically. In this work, we characterize ascorbic acid as a positive modulator of recombinant α9α10 nAChRs. Experimental Approach: ACh-evoked responses were analysed under two-electrode voltage-clamp recordings in Xenopus laevis oocytes injected with α9 and α10 cRNAs. Key Results: Ascorbic acid potentiated ACh responses in X. laevis oocytes expressing α9α10 (but not α4β2 or α7) nAChRs, in a concentration-dependent manner, with an effective concentration range of 1–30 mM. The compound did not affect the receptor's current–voltage profile nor its apparent affinity for ACh, but it significantly enhanced the maximal evoked currents (percentage of ACh maximal response, 240 ± 20%). This effect was specific for the L form of reduced ascorbic acid. Substitution of the extracellular cysteine residues present in loop C of the ACh binding site did not affect the potentiation. Ascorbic acid turned into a partial agonist of α9α10 nAChRs bearing a point mutation at the pore domain of the channel (TM2 V13′T mutant). A positive allosteric mechanism of action rather than an antioxidant effect of ascorbic acid is proposed. Conclusions and Implications: The present work describes one of the few agents that activates or potentiates α9α10 nAChRs and leads to new avenues for designing drugs with potential therapeutic use in inner ear disorders.